Penyelesaian Sengketa Perceraian Di Pengadilan Agama Pasca Pemberlakuan Sema Nomor 1 Tahun 2022 (Analisis Putusan Pengadilan Agama Painan Nomor 492/Pdt.G/2023/PA.Pn.) - Muhamad Ilham Azizul Haq; Yasniwati; Yaswirman (UNES Law Review, 2023)
This study aims to analyze the settlement of divorce disputes in religious courts after the implementation of the Circular Letter of the Supreme Court of the Republic of Indonesia Number 1 of 2022 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2022 as Guidelines for the Implementation of Tasks for the Courts dated December 15, 2022. The method used for this research is a normative legal research method that refers to literature research and laws, then data collection and analysis are carried out after which conclusions are drawn using the deductive method of thought. The results showed that, the issuance of the Formulation of the Religious Chamber number 1 letter b point 2) Circular Letter Number 1 of 2022 which stipulates that in an effort to maintain a marriage and fulfill the principle of making divorce difficult, divorce cases on the grounds of continuous disputes and quarrels can be granted if it is proven that the husband / wife is in continuous dispute and quarrel, or has separated the place of residence for at least 6 (six) months does not just appear but goes through a long process. The Supreme Court through the formulation of the Religious Chamber Meeting in Supreme Court Circular Letter 4 of 2014 also provides a number of indicators as a clue to the condition of a broken marriage. This is then refined in Supreme Court Circular Letter 3 of 2018 which provides instructions to judges to consider sufficiently and thoroughly in adjudicating divorce cases. The formulation of the Religious Chamber Meeting in Supreme Court Circular Letter 1 of 2022 emphasizes the provisions of Article 39 paragraph (2) of Law Number 1 of 1974 concerning Marriage which makes it easier for judges to explore the root causes of divorce filed by husband or wife to minimize the reasons for divorce of continuous disputes and quarrels.